Van Dijk Modelling on Critical Discourse Analysis (A Study on Mata Najwa Program â€˜Gara-Gara Tagarâ€™ In Trans 7 In September 5th 2018) - Sujatmiko Sujatmiko (Universitas PGRI Yogyakarta, 2020)
The television program of Mata Najwa on Trans 7, is well-known for its high rating, often invites public figures from society, politics and government. The program is used as a strategic media for groups of people from the background of social and politics, employing the oral designing, to influence publicâ€™s perception and opinion. As a result, it forms a particular discourse. A good discourse should not reveal various perception of the recipients. From every oral discourse being produced (either it is good or bad) will form various perception and drive publicâ€™s opinion. In this investigation, it focuses on Mata Najwaâ€™s â€œGara-Gara Tagarâ€ which was broadcast live on Wednesday September 5th 2018 in Trans 7. The study of discourse, in this research, employs Van Dijk modeling on critical discourse analysis whose perspective is that language has strong relationship with power, ideology and politics. Three research problems being investigated in this research are textual analysis (micro structure), super-structure analysis and social-contextual analysis (macro structure). This is qualitative research by conducting observation to gain the data. The results of this research are macro structure, super structure analysis and micro structure analysis. Discourse can be employed as a media to making opinion which influences publicâ€™s opinion through sentences, diction and language styles.